Globalization of education: art as a guarantor of identity preservation - Shramko Оксана (Actual Problems of Mind, 2023)
The article discusses the specific features of globalization transformations of education in the context of identity preservation and substantiates the role of art in this process. Emphasizing the negative features of globalization, such as unification and erosion of identity, the author turns to the search for ways to synchronize polar trends and considers R. Robertson’s glocalization strategy as one of the ascending ones in the search for an answer to the challenges of identity preservation that education faces today. The basis of such a strategy is the understanding of identity as a global value, and the leading principle is interpenetration and coherence of the idea of globalization and the idea of localization. Therefore, the basis of the strategy of glocalization in education should be the definition of identity as the main condition for mutual interest and complementarity of different localities that create a global educational space. This process requires an understanding of the specifics of globalization transformations in the field of education as a gradual movement from one-linearity and mono-subjectivity to a holistic worldview and worldview based on integration. At the same time, the principle of multiculturalism as an indivisible unity of two aspects: cultural pluralism and cultural individualism as respect for identity is gaining priority.The fundamental status of multicultural competence in the list of general competencies that define the profile of any educational program also seems obvious. Art is one of the most effective means of forming multicultural competence through the immanent function of emotive world involvement, thanks to which a person becomes a person capable of seeing and feeling the world through the eyes and sensations of the Other. Also, art itself most clearly demonstrates identical rootedness at the ethnic, national and cultural levels, which allows us to make assumptions about art as a guarantor of identity preservation in the process of globalization of education and art education as an important factor in the development of integraleducational programs based on the principles of multiculturalism.